The Effect of Good Corporate Governance on Banking Return on Assets on the Indonesian Stock Exchange with Firm Size as a Mediation Variable for the 2020-2023 Period - Kotten, Karan Immanuel; Arthana, I Komang; Natonis, Sari A. (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes the effect of Good Corporate Governance (GCG) on Return on Assets (ROA) of banks listed on the Indonesia Stock Exchange (IDX) during 2020–2023, with Firm Size as a mediating variable. The research is motivated by the decline in bank profitability during the COVID-19 pandemic due to increased credit risk and sluggish credit growth. Secondary data were collected from annual reports of eight major banks selected through purposive sampling. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping to test the significance of relationships between variables. The results show that GCG has a significant positive effect on both Firm Size and ROA, highlighting the importance of transparency, accountability, responsibility, independence, and fairness in enhancing asset efficiency and profitability. However, Firm Size does not significantly affect ROA and therefore does not mediate the relationship between GCG and ROA. These findings indicate that while GCG contributes to firm growth, larger scale alone does not ensure higher profitability without effective asset and risk management. The study supports Signaling Theory, suggesting that strong governance practices send more valuable market signals than operational scale. This research contributes to understanding the determinants of bank profitability during periods of crisis and emphasizes the managerial importance of strengthening governance and asset management efficiency rather than focusing solely on expansion.